Gambaran Trasncultural Self-Efficacy pada Perawat di Rumah Sakit Perkebunan Jember Klinik - Andika Firda Azza Zahra (Fakultas Keperawatan, 2025)
Introduction: In a multicultural society such as Indonesia, nurses must have transcultural self-efficacy (TSE)—the confidence to provide culturally sensitive care—to overcome communication barriers and avoid discrimination. Jember Perkebunan Hospital Clinic serves patients from diverse cultural backgrounds, including Javanese and Madurese, who have unique beliefs and health practices (e.g., the Suwuk and Nyapot traditions). Understanding nurses' TSE levels is crucial for improving care quality. This study aims to analyze nurses' TSE levels at Jember Perkebunan Hospital Clinic across three domains: cognitive, affective, and psychomotor. Methods: A descriptive cross-sectional study was conducted with 82 inpatient nurses selected via total sampling. Data were collected using the Transcultural Self-Efficacy Scale (TSET), adapted from Ferguson (2007), and analyzed univariately. Results: 76.8% of nurses demonstrated high TSE levels, while 22% and 1.2% had moderate and low levels, respectively. Domain-Specific Performance: Cognitive: 75.6% scored high, reflecting strong knowledge of cultural concepts. Affective: 81.7% scored high, demonstrating exceptional empathy and cultural sensitivity. Psychomotor: 78% scored high, indicating confidence in practical skills for cultural competence care. Conclusion: Most nurses at Jember Perkebunan Hospital Clinic demonstrate high TSE levels, particularly in affective competence. However, the presence of moderate and low TSE scores highlights the need for targeted training to strengthen cultural competence, especially in the cognitive and psychomotor domains. These findings emphasize the importance of institutional support to maintain and enhance cultural competence nursing practices.
Entry oleh Arif 2026 Februari 10
Keywords: Cultural competence; nurses; transcultural nursing; transcultural selfefficacy